Relação entre estado nutricional e desempenho cognitivo de idosos - Cardoso, Juliana de Fatima Zacarin (2019)
With the longevity of the population increases the prevalence of cognitive alterations in the elderly at the same time that the nutritional state also undergoes changes. The objective of this research was to verify cognitive factors associated to the poor nutritional status of the elderly attended in the primary health care services of a city in the interior of São Paulo. This is a cross-sectional study, with descriptive, correlational and association analyzes performed with a sample composed of 234 participants. The data were collected in the homes of the elderly and were used: Instrument of sociodemographic characterization, Mini Evaluation of the Nutritional State-MAN, Addenbrooke-ACE-R Cognitive Exam, and International Questionnaire of Physical Activity - IPaq. The results showed that the majority of the sample consisted of women (67.9%), with a mean age of 69.55 years, married or living with partners (59.4%). The majority of the elderly evaluated presented signs of cognitive impairment (54.3%) and adequate nutritional status (85.5%). Older people with inadequate nutritional status (malnourished or at risk of malnutrition) presented worse performance in the cognitive evaluation, when compared with the elderly with adequate nutritional status. There was a positive correlation between MAN scores and cognitive tests (ACE-R total: 0.339; r <0.001; Attention and Guidance: 0.220; r = 0.001; Memory: 0.333; r <0.001; Verbal Fluency: 0.268; <0.001; Language: 0.258; r <0.001; Visuo-spatial: 0.278; r <0.001). Among the factors associated with nutritional status, the analyzes showed that global cognitive performance (p = 0.001) and all cognitive domains: Attention and Guidance (p = 0.001), Memory (p = 0.002), Verbal Fluency ), language (p = 0.008) and visuospatial ability (p <0.001) were positively associated with nutritional status. Insufficient practice of physical activity and use of more medications were negatively associated with nutritional status. It is concluded, therefore, that the cognitive performance is correlated to the nutritional state, being that the global cognitive performance and the specific domains present as protective factors to the nutritional state.